Solenoptera Audinet-Serville, 1832 (Coleoptera, Cerambycidae, Prioninae, Solenopterini) in Cuba, with description of a new species - Devesa, Sergio; Fonseca, Elier; Barro, Alejandro (Zootaxa, 2016)
The genus Solenoptera Audinet-Serville in Cuba is reviewed and S. zayasi sp. nov. is described from Cuba. The following nomenclatural changes are proposed: 1) S. fraudulenta Galileo & Martins, 1993 is synonymized with S. dominicensis Gahan, 1890; 2) S. cubana (Zayas, 1975) is transferred from Prosternodes cubanus Zayas, 1975. Furthermore, S. dominicensis is removed from the Cuban fauna and new localities for S. cubana are recorded. A key to all three Solenoptera species known from Cuba, both for males and females, is included.